The ectomycorrhizal basidiomycete Laccaria bicolor releases a GH28 polygalacturonase that plays a key role in symbiosis establishment - Zhang, Feng (The New phytologist, 2022)
© 2021 The Authors. New Phytologist © 2021 New Phytologist Foundation.